Female image in glossy magazines for men in Russia and Abroad: education and class - Beloedova, Anna V.; Novinkina, Ekaterina A.; Richter, Margarita S. (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The article deals with a comparative and educational analysis of the specifics of the presentation and functioning of a female image in advertising for men's glossy magazines MAXIM and Esquire in the USA, Russia and Sweden. As a result of typological analysis, it was revealed that MAXIM is a narrowly targeted publication of an erotic nature, Esquire is a publication of general interest. At the same time, magazines of the same brand in different countries are similar in audience orientation, purpose, main headings, frequency, only the circulation volume differs significantly. The results of the content analysis and the comparative method indicated that the American and Russian MAXIM often sexually objectifies a woman, presents her image in advertising through the prism of gender stereotypes. Esquire magazine in the USA, Russia and Sweden exploits female images much less often, trying to build an image of collegial relationships between the sexes.